2001
DOI: 10.1080/09553000110069335
|View full text |Cite
|
Sign up to set email alerts
|

Proliferating cell nuclear antigen (PCNA): ringmaster of the genome

Abstract: Proliferating cell nuclear antigen (PCNA) protein is one of the central molecules responsible for decisions of life and death of the cell. The PCNA gene is induced by p53, while PCNA protein interacts with p53-controlled proteins Gadd45, MyD118, CR6 and, most importantly, p21, in the process of deciding cell fate. If PCNA protein is present in abundance in the cell in the absence of p53, DNA replication occurs. On the other hand, if PCNA protein levels are high in the cell in the presence of p53, DNA repair ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
204
1
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(226 citation statements)
references
References 123 publications
17
204
1
4
Order By: Relevance
“…It has been reported that analysis of PCNA protein expression could play an important role in the prediction of long term survival and prognosis of patients. PCNA has been reported as the ring master of the genome due to active participation in several molecular pathways responsible for the survival and death of mammalian cells (Paunesku et al, 2001). Overexpression of PCNA has been reported in several cancers including oral cancer (Manojprabhakar et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that analysis of PCNA protein expression could play an important role in the prediction of long term survival and prognosis of patients. PCNA has been reported as the ring master of the genome due to active participation in several molecular pathways responsible for the survival and death of mammalian cells (Paunesku et al, 2001). Overexpression of PCNA has been reported in several cancers including oral cancer (Manojprabhakar et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Furthermore, upregulation of PCNA in Reh cells may enhance DNA replication but was probably a result of IR induced DNA repair in our study. 35 Temporal expression profiles may give information about the onset of gene regulation in relation to when the phenotypic changes are detected. Cell cycle arrest was detectable earlier than 4 hr after IR, whereas more than 10 hr were required before significant apoptosis was seen.…”
Section: Discussionmentioning
confidence: 99%
“…PCNA has been called the ''ringmaster of the genome,'' because this 29-kDa protein has been shown to actively participate in a number of the molecular pathways responsible for the life and death of the mammalian cell (10). There are a number of reports in the literature suggesting that PCNA is, itself, posttranslationally modified, although there is some conflict as to what these modifications may be (11)(12)(13)(14).…”
mentioning
confidence: 97%